The effects of variable nitrogen application on barley starch structure under drought stress. Issue 4 (17th September 2015) - Gous, Peter W.; Warren, Frederick; Mo, Oi Wan; Gilbert, Robert G.; Fox, Glen P.
<x xml:space="preserve">Abstract</x> Under well‐watered conditions, agronomic yield increases have been observed to correlate with nitrogen supply. Thus there is a need for proper fertilizer regimes to increase both metabolic and regulatory processes during kernel development in cereal crops. However, the impact of varying levels of nitrogen application on starch biosynthesis, structure and properties in grain under drought stress is not well known. This study examines the impact of different nitrogen application rates, in conjunction with drought stress, on starch biosynthesis in barley (Hordeum vulgare L.) grain. The proportions of short amylopectin branches and long amylose branches in the grain of Fitzroy and Grout were higher under drought stress with high nitrogen. This suggests that starch biosynthesis was affected, probably owing to early termination of grain fill. These changes in the long branches can affect starch properties, such as the rates of enzymatic degradation, and hence fermentability and nutritional value. In contrast, the chain length distribution (CLD) of the debranched starch from the grain grown under favourable conditions (Hermitage) did not show the same level of qualitative variations among the nitrogen treatments. The similar CLDs between these grain samples suggest that starch biosynthesis was not negatively impacted by the different nitrogen applications. However, with the grain under drought stress conditions, the results indicate that starch biosynthesis and quality could be impacted by nitrogen application. This has the potential to give rise to beneficial structural changes that are useful for some value‐added products. Copyright © 2015 The Institute of Brewing & Distilling